”Profana gravar” i medeltidens Lund - Carelli, Peter (Hikuin, 2000)
“Profane graves” in medieval Lund By Peter Carelli More than 10,000 medieval graves have been documented in one way or another in connection with excavations in what was once cemetery ground in the town of Lund. The material from the graves shows relatively large uniformity regarding burial practices. About thirty burials, however, differ significantly from the great mass of graves in that they were found outside the cemeteries in purely profane contexts. Since these graves differed so strikingly from the normal Christian burial customs, which were regulated by generally known standards and rules, there must have been very special reasons for the choice of this “profane” style of burial. In this connection it is important to emphasise that the choice of burial form was influenced by the deeds of the deceased and by the choices and actions of the people who buried the body. By studying the profane grave material contextually and morphologically, it has been possible to divide the graves into two main groups, depending on whether they were occasioned by private or public motives. The private motives are of a purely personal character: a murderer who tried to hide his victim, a mother who hid her stillborn child, or relatives who buried a suicide. What they have in common is that the individual events made it impossible to have a normal Christian burial. The public motives are instead an expression of the punitive rights of the executive powers. Mutilations, executions, and desecrations were punishments that could be meted out for particularly serious crimes against society, such as counterfeiting.